Islamic Legal Perspectives on Climate Justice: Integrating Environmental Ethics and Economic Responsibility - Zeynaddin Musennif Shabanov; Gulay Yusifli Elshad; Elshad Yusifov (Journal of Islamic Law and Legal Studies, 2025)
This study explores Islamic legal perspectives on climate justice by integrating environmental ethics with economic responsibility within the wider framework of Sharia. Using a qualitative library research approach, it examines classical sources such as the Qur’an, Hadith, and uṣūl al-fiqh, alongside contemporary works on Islamic environmental ethics, sustainable development, and climate governance. The findings show that Islamic principles—including khalifah (stewardship), mīzān (balance), ‘adl (justice), and maslahah (public interest)—provide a strong ethical foundation for addressing climate change and preventing environmental corruption (fasād). The Maqāṣid al-Sharī‘ah, particularly the preservation of life, property, lineage, and the environment, support environmentally conscious policies and sustainable economic practices. Islamic finance instruments such as green sukuk and ESG-aligned investments further promote ecological responsibility. Overall, Islamic legal and economic traditions offer a comprehensive framework that links environmental sustainability with socio-economic equity, positioning Islamic thought as an important contributor to global climate justice discourse.